A molecular mechanics study for selective complexation of metal ions in medical applications - Chantson, Tracy, Elizabeth (My University, 1994)
Molecular mechanics calculations are used to interpret and predict metal ion discrimination by coordinating ligands. Of particular interest are chelates exhibiting characteristics that Single them out for potential medical application; Selectivity patterns for several series of ligands are investigated with the help of strain energy profiles as a function of metal-donor atom bond distance. Ligands include simple; open-chain oxygen- and nitrogen-donors ana triaza- and tetraazamacrocyeles. Results are compared with X-ray crystallographic and solution data. Factors such as chelate ring size, conformational flexibility and preferred metal coordination geometry are found to influence metal specificity. Addition of pendent donor groups to macrocyoles leads to rigid structures and selectivity predictions according to cavity size. Interpretation of specific. metal ion recognition by polyetner antibiotics is attempted. Structural and steric factors are probed as possible determinants of metal choice. both covalent and ionic bonding models are explored. The covalent approach results in predictions of metal selectivity which correlate with mown selectivity patterns. Unfortunately, inability to optimise force field parameters in the ionic bonding approach forced us to abandon this model. The main force field used is the TRIPOS (1992,1993) force field. It performs well in calculations involving a univariate scanning technique but has to be modified to obtain reasonable structure reproduction with the large antibiotics, Errors in thermodynamic data predictions are obtained, nonbonding parameters have yet to be properly parameterized and the allocation of partial atomic charges warrants closer examination . All of these factors contribute to the poor performance of the force field when ionic interactions between metal and donor atoms of the polyethers are assumed.
A dissertation submitted to the Faculty of Science University of the Witwatersrand, Johannesburg for the degree of Master of Science. Johannesburg, 1994.
Keywords: Ligands; Chelates; Metal ions; Ligands; Antibiotics--Research